Association of Toll-like receptor 4 Signaling Pathway with Steroid-induced Femoral Head Osteonecrosis in Rats - 田雷 周东生 王坤正 张伟 时志斌 樊立宏 孙水 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Osteonecrosis of the femoral head is frequently observed in patients treated with excessive corticosteroids. However, the pathogenesis of corticosteroid-induced osteonecrosis remains unclear. The purpose of this study was to investigate the role of Toil-like receptor 4 （TLR4） signaling pathway in steroid-induced femoral head osteonecrosis in rats. Male Sprague-Dawley rats were injected intramus- cularly with 20 mg/kg methylprednisolone （MP） for 8 weeks, twice per week. The animals were sacri- ficed at 2, 4 and 8 weeks after the last MP injection, respectively, and then allocated to the 2-, 4- and 8-week model groups （n=24 each）. Rats in the control group （n=12） were not given any treatment. Histopathological analysis was performed and the concentration of tartrate-resistant acid phosphatase （TRAP） in plasma was determined. The activation of osteoclasts in the femoral head was assessed by TRAP staining. The expression of TLR4, MyD88, TRAF6 and NF-Id3 p65 that are involved in TLR4 signaling, and MCP-1 production were detected by using real-time PCR （RT-PCR） and Western blotting. The results showed that the osteonecrosis in the femoral head was clearly observed and the concentra- tion of TRAP in the plasma was increased in the model rats. The femoral head tissues in MP-treated rats were positive for TRAP and the intensity of TRAP staining was greater in MP-treated rats than in con- trol rats. As compared with the control group, the mRNA expression of TLR4 signaling-related factors was enhanced significantly at 4 and 8 weeks, and the protein levels of these factors increased signifi- cantly with time. It was concluded that MP could induce the femoral head osteonecrosis in rats, which was associated with osteoclast activation via the TLR4 signaling pathway. These findings suggest that TLR4 signaling pathway plays a pivotal role in the pathogenesis of steroid-induced osteonecrosis.